PERANGKAT EKSTRAKSI JAHE TERINTEGRASI BERBASIS ARDUINO UNO DENGAN PENGUJIAN METODE SPEKTROFOTOMETRI VISIBEL - Sulistyo Widodo; Randy Rahmanto; Belinda Ayuningtyas (Jurnal Teknik dan Science, 2024)
The Automatic Ginger Extractor Based on Arduino Uno consists of three main units: the input unit, the processing unit, and the output unit. The input unit is equipped with Up, Down, and Ok buttons for navigation, as well as a phototransistor sensor that detects the presence of ginger samples (ginger simplicia) to be extracted. The processing unit uses an Arduino Uno microcontroller to process signals from the sensor and control the output unit. The output unit includes a motor driver, a power window motor for operating the grinder to crush the samples, a 12V DC motor for operating the stirrer to mix the samples with the solvent, an electric solenoid valve for dispensing the extract, and an LCD to display the process status. The working principle of this device is that when the phototransistor sensor detects a sample, the sensor signal activates the power window motor to grind the ginger. The user can then manually set the dissolution time using the navigation buttons. The longer the dissolution time, the better the extraction result. The final product is a liquid containing curcumin, which is measured using a curcumin content meter to determine its concentration. The device shows an error rate of 2.74% compared to manual methods. With this design, the Arduino Uno-based automatic ginger extractor offers a more efficient and consistent extraction process. The automation system allows for better control and optimal results with minimal manual intervention.